Avaliação do cultivo de melancia submetida a doses de nitrogênio e pré-cultivos de espécies de plantas em sucessão - Carmo, Ignácio Lund Gabriel da Silva (2017)
The state of Roraima in 2015, produced 28,621 tons in 1,337 ha of planted area and with productivity of 21,40 t ha-1, this productivity is considered low considering the potential of the crop. The reasons for this are related to the inadequate management, mainly to the monoculture crop and the low fertility of the soils. The present work aimed to determine alternative systems of crop succession and nitrogen doses suitable for irrigated watermelon cultivation in the cerrado of Roraima. Nitrogen doses (0, 75, 150 and 225 kg ha-1) were tested in watermelon culture, combined with three crop succession systems. The design was used in randomized blocks, in the scheme of subdivided plots with four replicates. The plots were constituted by the successor plant species (spontaneous vegetation + corn, Urochloa ruziziensis + corn and pigeon bean + maize) and the subplots by nitrogen doses (0, 75, 150, 225 kg ha-1). in the watermelon the fruit yield, the number of fruits ha-1, the average mass per fruit, the percentages of fruits with mass between 5 and 10 kg and fruits greater than 10 kg, soluble solids (°Brix), ph and acidity titrated. The values of the variables were submitted to analysis of variance with application of the F test at the 5% probability level. The averages for the effects of the years of cultivation and of the predecessor species were compared by the Tukey test at 5% and those referring to the effects of the nitrogen doses were done by regression analysis. the pigeon bean increases the total number of fruits ha-1, number of ha-1 fruits with mass ≥ 10 kg and yield of watermelon fruits, the average dose of n in the range of 118 to 124 kg ha-1 of n favors the higher number of fruits ha-1 number of fruits ha-1 with mass ≥ 10 kg and average solids soluble in the pulp of watermelon fruits, the quality of watermelon fruits are influenced by the crop years, predecessor plants and the doses of n. The pigeon pea and U. ruziziensis can be cost-effective hedges to increase soil nitrogen availability for the next crop.